1976
DOI: 10.2307/1960328
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Building as a Comparative Political Process

Abstract: Agenda building is the process through which demands of various groups in a population are translated into issues which vie for the attention of decision makers (formal agenda) and/or the public (public agenda). This paper presents three models for the comparative study of agenda building. The outside initiative model describes groups with minimal prior access to decision makers, who must consequently first expand their issues to a public agenda before they can hope to reach the formal agenda. The mobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
166
0
25

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(191 citation statements)
references
References 21 publications
0
166
0
25
Order By: Relevance
“…Some 35 years of agenda-setting literature from American scholars of public policy have provided the concepts of 'policy streams' and 'windows of opportunity' (Kingdon 1984), the importance of 'policy images' and 'institutional venues' (Baumgartner and Jones 1991 and the notion of 'issue careers' (Cobb et al 1976). The literature which is applied to EU policymaking is, however, in its relative infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Some 35 years of agenda-setting literature from American scholars of public policy have provided the concepts of 'policy streams' and 'windows of opportunity' (Kingdon 1984), the importance of 'policy images' and 'institutional venues' (Baumgartner and Jones 1991 and the notion of 'issue careers' (Cobb et al 1976). The literature which is applied to EU policymaking is, however, in its relative infancy.…”
Section: Introductionmentioning
confidence: 99%
“…existen condicionantes estructurales que limitan el diseño e implementación de políticas de gestión de riesgos. Se presenta en adelante el proceso de jerarquización de la gestión de riesgo de inundaciones en la agenda pública (Cobb, Ross y Ross, 1976) atendiendo a que el ingreso del problema de las inundaciones a la agenda pública es un sedimento de la problematización pública del posdesastre.…”
Section: El Momento Instituyente Problematización Pública De Las Inununclassified
“…A 2004 'Listening to Canadians' poll conducted by the Canadian government (available through the Canadian Opinion Research Archive) found that 84 % of those surveyed heard about the content of the Throne speeches through the media (print, television and radio), versus only 7.5 % who actually read the speech or watched it being delivered. People may not always think an issue is important while politicians, policy experts and activists expand the political rhetoric surrounding an issue (Cobb et al;Oldendick and Bardes 369;Hill and Hinton-Anderson 925;Stimson et al, 1994). Issue salience is an important factor to consider in explaining the role of politicians, interest organisations and public opinion on issue framing and policy outcomes.…”
Section: Public Preferences and Issue Saliencementioning
confidence: 99%